New vaccines on the horizon - Arsenović-Ranin Nevena (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2019)
Vaccines are considered to be one of the greatest public health achievements of the last century. As a result of widespread vaccine use, the smallpox virus has been completely eradicated and the incidence of other diseases such as polio, measles, tetanus and diphtheria has been drastically reduced. Current licensed vaccines, predominantly composed of either live attenuated or killed pathogens, pathogen subunits, owe their success to their ability to elicit neutralizing antibodies against pathogens. On the other side, cell-mediated immunity, which plays a central role in elimination of intracellular pathogens (which in most cases leads to chronic infections) is much more difficult to obtain using current vaccines. Currently, numerous vector and nucleic acid (DNA and mRNA)-based prophylactic vaccines, capable of inducing substantial vaccine-specific T cell responses, are investigated in preclinical and clinical studies, with promising results. This review focuses the background of vector and nucleic acid-based vaccines, their strengths and weaknesses and safety issues.